THE EFFECTIVENESS OF DEBATE METHOD TO IMPROVE STUDENTS’ SPEAKING SKILL - MUSFIRAH, MUSFIRAH (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This study presents research about the effectiveness of debate method to improve students’ speaking skill to the students of second grade of exact of MA in Islamic Boarding School Al-JunaidiyahBiru Bone. In conducting the study, the researcher used quantitative method because the researcher conducted the data in form of numbers. And the way collected data by using pre-experimental design with pre-test and post-test and questionnaire. The purpose of this method was to carry out an experiment whether teaching speaking by using debate method if effective to the students’ speaking skill or not. After the data was collected and the result of the test was obtained to prove the hypothesis and to establish the validity, the researcher analyzed the value of t-observation. It was proved by the result of students’ test. The table showed that the mean score obtained by the students in the post-test (2.470) was greater than the mean score of the students in pre-test (1.529). The data of score of interest through questionnaire indicated that eight students or 47.058% whose score were in very high, seven students or 41.176% whose score were in high, two students or 11.764% whose score were in moderate. Debate method gave better result to improve the students’ speaking skill. In other words, debate method was effective and interesting to use in teaching English speaking.